Receivables from employment through judicial practice - Mitrović Igor (Trendovi u Poslovanju)
The paper deals with the issue of legal regulation of judicial protection of labor rights and the application of substantive law in proceedings of this kind before the courts in the Republic of Serbia. Given that legal security is one of the essential attributes of the rule of law in the legal order of a state, proper application of substantive law by acting courts of general and special jurisdiction is of crucial importance in this regard. In the paper, particular emphasis is placed on the inequality of court practice, as well as on the consequences that this inequality of court practice creates for the legal order of the state in general; what are the consequences of unequal and inconsistent interpretation of the law by courts, and in what way it is necessary to respect the basic principles on which the right to a fair trial is based upon, and an independent and impartial tribunal, which represents the basic principles of the rule of law and legal safety of all citizens.